Advances in biofuels - Pogaku, Ravindra; Sarbatly, Rosalam Hj. (New York, N.Y. : Springer, 2013)
Biofuels will play a key role in the 21st century as the world faces two critical problems; volatile fuel prices and global climatic changes. Both of these are linked to the overdependence on the fossil fuels: petroleum, natural gas, and coal. Transportation is almost totally dependent on petroleum based fuels such as gasoline, diesel fuel, liquefied petroleum gas, and on natural gas. Despite a significant amount of research into biofuels, the field has not been able to replace fossil fuels. Recent advances will change this scenario. Extracting fuel from biomass has been very expensive (both monetarily and in land usage), time consuming, unusable byproducts, etc. Technology to obtain liquid fuel from non-fossil sources must be improved to be faster, more efficient and more cost-effective. This book will cover the current technology used for a variety of plant types and explore shortcomings with each.
Includes bibliographical references and index.
Keywords: Biomass energy; Biomass conversion; Biodiesel fuels